The 2022 Hormozgan Doublet Earthquake: Two Blind Thrusts‐Related Folding in Zagros Fold‐And‐Thrust Belt, Southeast Iran. Issue 4 (11th February 2023) - Yang, Ying‐Hui; Li, Xiaoyun; Hu, Jyr‐Ching; Song, Jiawei; Zhao, Jingjin; Yassaghi, Ali; Pathier, Erwan; Xu, Qiang; Chen, Qiang
Abstract: A doublet earthquake event including two main shocks with a magnitude larger than M w 6.0 occurred on 1 July 2022 in the Zagros fold‐and‐thrust belt, southeast Iran. The coseismic InSAR deformation field shows that this event caused significant surface uplift due to fault‐related folding in the seismic zone. The estimated preferred faulting model suggests that a higher dip angle fault (maximum slip of ∼1.1 m), and an overlying gentle dipping fault (maximum slip of ∼1.2 m) within the Bandar‐e‐Lengeh Anticline, are responsible for the first and second main shocks, respectively. The calculated Coulomb failure stress change suggests that the first main shock and its M w 5.7 aftershock have a significantly positive triggering effect in the second main shock. The accumulated interseismic strain should have been partly released by the two main shocks. Finally, the salt diapir activity may affect the generation of the earthquake in the seismic zone. Plain Language Summary: The doublet earthquake frequently occurred in the southeast part of the Zagros fold‐and‐thrust belt in the past years. In this study, we first adopted the Synthetic Aperture Radar images captured by Sentinel‐1 satellite to map the coseismic surface deformation of the 2022 Hormozgan doublet earthquake. The uplift of fault‐related folding controls the coseismic surface motion of these events from blind thrusting. Moreover, the two main shocks are caused by the rupture of two faults within the Bandar‐e‐Lengeh Anticline. Furthermore, the first main shock increased the stress in the source area of the second main shock, and positive triggered the rupture of the seismogenic fault of the second main shock. The interseismic surface deformation suggests that the 2022 Hormozgan doublet earthquake may have released the accumulated interseismic strain for the past ∼104 years. In addition, salt diapir activity in the southeast part of the seismic zone may contribute to the 2022 Hormozgan doublet earthquake. Key Points: A doublet earthquake occurred in the southeastern of Zagros fold‐and‐thrust belt with a significant salt layers activity A combination of steep and shallow blind faults is responsible for the 2022 Hormozgan doublet earthquake The interseismic strain accumulation and salt diapir activity in the southeast of the seismic zone may cause this doublet earthquake